2021
DOI: 10.2147/rmhp.s316795
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Musculoskeletal Diseases of the Upper Extremity Among Dental Professionals in Germany

Abstract: Objective Although many findings on occupational musculoskeletal complaints are available from American and European dentists, the corresponding data from Germany are still scarce. Therefore, the aim of this study was to provide additional information on the prevalence of and risk factors for musculoskeletal disorders of the upper extremity, particularly the shoulder in this specific population. Methods A written survey was carried out among 600 dentists in the state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…However, it is also likely that more experienced orthodontists have already adapted to work positions that avoid the presence of MSDs. 4 One study carried out in Germany 22 found that the years of work showed to increase the percentage of MSDs. This situation could be related with a greater workload because patients seek to be treated by a more experienced professional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also likely that more experienced orthodontists have already adapted to work positions that avoid the presence of MSDs. 4 One study carried out in Germany 22 found that the years of work showed to increase the percentage of MSDs. This situation could be related with a greater workload because patients seek to be treated by a more experienced professional.…”
Section: Discussionmentioning
confidence: 99%
“…This situation was found in a German study where the stress level was a very important factor related with the presence of MSDs. 22 In this study, other variables that showed a positive correlation with the presence of MSDs were considered, such as the absence of several contracts and dissatisfaction with the job. However, due to the little literature and the type of study that was carried out, it was not possible to make accurate comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, various factors were controlled for, and only participants who had a high willingness to participate, were very cooperative, and had a high understanding of its purpose were included. In addition, it is difficult for participants recruited in the present study to represent the results of various age and sex groups [ 33 ]. With increasing age, musculoskeletal disorders may increase, which may affect muscle fatigue and activation during certain activities.…”
Section: Discussionmentioning
confidence: 99%
“…Darüber erhöht eine einseitige Belastung des Schultergürtels z. B. bei Schwimmern oder Personen, deren berufliche Tätigkeit ein Verharren in gebeugter und gedrehter Haltung erfordert, die Auftretenswahrscheinlichkeit für Schulterschmerzen 5 6 7 8 .…”
Section: Zusammenfassungunclassified